The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1161/circimaging.111.972406
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Velocity Vector Imaging Echocardiography With Magnetic Resonance Imaging in Mouse Models of Cardiomyopathy

Abstract: Background Myocardial strain imaging using echocardiography can be a cost-effective method to objectively quantify ventricular wall motion but few studies have compared strain measured with echocardiography against MRI in small animals. Methods and Results We compared circumferential (CS) and radial strain (RS) measured with echocardiography (vector velocity imaging [VVI]) to displacement encoding with stimulated-echo (DENSE) MRI in two mouse models of cardiomyopathy. In 3 month old mice with gene targeted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…47,48 Despite these limitations, the correlation between tissue tracking strain values from both techniques is similar to previously published data for both modalities. 6,49 Moreover, the substantial concordance in patient characterization suggests potential diagnostic value.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 Despite these limitations, the correlation between tissue tracking strain values from both techniques is similar to previously published data for both modalities. 6,49 Moreover, the substantial concordance in patient characterization suggests potential diagnostic value.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Specifically the recent growth in tissue tracking software allows myocardial functional data to be extracted from both echocardiography and CMR images with equal ease and accuracy. [6][7][8] An emphasis on intermodalbetween May 2006 and May 2013. This included 28 patients with CP, 30 patients with RCM, and 34 control patients who had no structural or functional abnormality on echocardiography or CMR.…”
mentioning
confidence: 99%
“…In their work, Azam et al demonstrated that although echocardiographic vector velocity imaging seemed to be feasible and accurate, strains measured with DENSE method were more variable than those measured with MRI with similar variability for radial and circumferential strains [12].…”
Section: Taggingmentioning
confidence: 99%
“…Thus, it should be stressed that further analyses of the proposed model should be performed in terms of diagnostic assessment methods, including not only ultrasonography but also MRI. Yet, at this point of acute analysis, it was more important to use noninvasive methods only, with no additional stress from MRI contrast enhancement and prolongation of the postoperative anesthesia time, yet still reliable data acquisition [23,24,25]. …”
Section: Discussionmentioning
confidence: 99%